Development in Origanum ssp.: a simple phenological scale todetermine thermal time requirements to critical reproductive events - Davidenco, Vanina; Vega, Claudia Rosa Cecilia; Piccardi, Mónica Belén; Argüello, Juan Alberto (2018)
Origanum spp. is commercially important as a main aromatic herb. However, little eco-physiological information is available regarding plant development and its control by genotype and environmental factors. Here, we aimed at developing (i) a simple phenological scale based on morphological features in common of the genus and (ii) a model that allows quantifying the thermal time requirements for critical events, such as vegetative to reproductive transition (V3) and flowering (R6). Plants of O. vulgare ssp. vulgare (O. Compacto) and O. vulgare ssp. hirtum (Ietsw.) (O. Criollo) were evaluated through sequential observations of bud development. Despite genotypic differences in morphology, a robust key was built to describe main vegetative and reproductive stages. The resulting scale comprises seven phenophases, from V0 to V3 (vegetative stages) and from R4 to R6 (reproductive stages). Phenological stages V3 and R6 showed to be critical, because they represent the time to transition from vegetative to reproductive phases, and full blooming, respectively. Phenology modelling based on thermal requirements was accurately described by logistic curves in both subspecies. Subspecies differed in the thermal time requirement to V3 and R6 (lower in O. Compacto). This key is a generic tool with potential use in crop eco-physiological studies because it can describe main developmental phases without taking into account morphology or cycle length.